Characterization of Dunaliella salina strains by flow cytometry: a new approach to select carotenoid hyperproducing strains - Mendoza, Hector (2014)
In the present work the characterization of different strains of Dunaliella salina from established cell culture collections and various isolates from solar saltworks located in the Canary Island, as well as one mutant, was carried out in order to assess the existence of intraspecific differences and to determine the potential productivity of each one. Morphological characteristics such as cellular size and cellular complexity and parameters linked to cellular physiology, such as pigment content or cellular growth rate, were determined by means of traditional techniques as well as flow cytometry. Results showed a high morphological and physiological intraspecific variability among the studied strains. Results suggest that the application of the lipidic dye Nile red allowed the development of a cytometric method faster than the traditional techniques to select carotenoid hyperproducing strains of microalgae.